Predictors of Return to Normal Neurological Function After Surgery for Moderate and Severe Degenerative Cervical Myelopathy: An Analysis of A Global AOSpine Cohort of Patients. Issue 5 (30th May 2019) - De la Garza Ramos, Rafael; Nouri, Aria; Nakhla, Jonathan; Echt, Murray; Gelfand, Yaroslav; Patel, Smruti K; Nasser, Rani; Cheng, Joseph S; Yassari, Reza; Fehlings, Michael G
Abstract: BACKGROUND: Multiple studies have established the safety and efficacy of surgical intervention for degenerative cervical myelopathy (DCM). Although the main goal of surgery is symptom stabilization, a subset of patients achieves remarkable improvements. OBJECTIVE: To identify predictors of return to normal neurological function after surgery for moderate or severe DCM. METHODS: This is an analysis of 2 prospective multicenter studies (the AOSpine CSM-North America and CSM-International studies) conducted between 2005 and 2011. For patients with complete preoperative magnetic resonance imaging (MRI) and 2-yr follow-up, characteristics were compared between those who achieved a modified Japanese Orthopaedic Association (mJOA) score of 18 at 2 yr (no signs of myelopathy) vs controls. Only patients with baseline mJOA ≤ 14 (moderate and severe myelopathy) were included to minimize ceiling effects. RESULTS: A total of 51 patients (20.3%) out of 251 with moderate or severe baseline myelopathy achieved an mJOA score of 18 at 2 yr. On stepwise multiple logistic regression analysis, T1-weighted (T1W1)-hypointensity (odds ratio [OR] 0.10; 95% confidence interval [CI], 0.01-0.79; P  = .03) and longer walking time on the 30-m walking test (OR 0.95; 95% CI, 0.92-0.99; P  = .03) were independent predictors of outcome, with an area under the curve of 0.71 for the model. CONCLUSION: In this study, T1W-hypointensity on MRI and longer walking time were found to predict a less likelihood of achieving return to normal neurological function after surgery for moderate or severe DCM. These findings may provide useful information for patient counseling and perioperative expectations.